Preconditioning with L-alanyl-L-glutamine in a Mongolian Gerbil model of acute cerebral ischemia/reperfusion injury - Pires,Vilma Leite de Sousa (2011)
PURPOSE: To investigate the effect of L-alanyl-L-glutamine (L-Ala-Gln) preconditioning in an acute cerebral ischemia/reperfusion (I/R) model in gerbils. METHODS: Thirty-six Mongolian gerbils (Meriones unguiculatus), (60-100g), were randomized in 2 groups (n=18) and preconditioned with saline 2.0 ml (Group-S) or 0.75g/Kg of L-Ala-Gln, (Group-G) administered into the femoral vein 30 minutes prior to I/R. Each group was divided into three subgroups (n=6). Anesthetized animals (urethane, 1.5g/Kg, i.p.) were submitted to bilateral occlusion of common carotid arteries during 15 minutes. Samples (brain tissue and arterial blood) were collected at the end of ischemia (T0) and after 30 (T30) and 60 minutes (T60) for glucose, lactate, myeloperoxidase (MPO), thiobarbituric acid reactive substances (TBARS), glutathione (GSH) assays and histopathological evaluation. RESULTS: Glucose and lactate levels were not different in studied groups. However glycemia increased significantly in saline groups at the end of the reperfusion period. TBARS levels were significantly different, comparing treated (Group-G) and control group after 30 minutes of reperfusion (p<0.05) in cerebral tissue. Pretreatment with L-Ala-Gln promoted a significant increase in cerebral GSH contents in Group-G at T30 (p<0.001) time-point compared with Group-S. At T30 and T60, increased levels of GSH occurred in both time-points. There were no group differences regarding MPO levels. Pyknosis, presence of red neurons and intracellular edema were significantly smaller in Group-G. CONCLUSION: Preconditioning with L-Ala-Gln in gerbils submitted to cerebral ischemia/reperfusion reduces oxidative stress and degeneration of the nucleus (pyknosis) and cell death (red neurons) in the cerebral tissue.